Scientific studies of halal food additives for consumption and good for health - Fermanto Fermanto; Muhammad Athoillah Sholahuddin (Journal of halal product and research (JPHR), 2020)
Food additives or food additives is one of the ingredients that are commonly used by humans to improve the taste, texture, appearance and color of food. Food additives are often used. The use of food additives or food additives aims to improve the quality of the final product and increase the shelf life of food ingredients. Food additives can be synthetic or derived from plants or animals, and they have been grouped by the World Health Organization and the Food and Agricultural Organization into three broad categories (flavor enhancers, enzymes and others), based on their function. However, at present the majority of people use food additives to the food excessively, thus creating a risk to health. Limit consuming food additives need to be considered when using it to be safe and not cause health problems. In addition, the majority of the food additive industry uses raw materials for food additives in the form of synthetic or artificial products so that if consumed in excess is harmful to health. One solution to reduce the consumption of synthetic food additives is to use natural food additives or natural food additives which when used are considered safe for consumption and certainly good for health